A novel gene-activated matrix composed of PEI/plasmid-BMP2 complexes and hydroxyapatite/chitosan-microspheres promotes bone regeneration - Ding, Ruyuan; Liu, Yajun; Cheng, Dawei; Yang, Gang; Wu, Wenjing; Du, Haoran; Jin, Xin; Chen, Yihan; Wang, Yuanyin; Heng, Boon Chin *; Xu, Jianguang (Springer, 2022)
The incorporation of pro-osteogenic growth factors into bone graft materials to enhance bone regeneration is a key research area within the field of bone tissue engineering and regenerative medicine. However, growth factors directly incorporated in protein form are easily degraded, and have a limited active half-life, which cannot exert long-term and stable osteoinductive and oteoconductive effects. The combination of gene therapy and tissue engineering through gene-activated matrix (GAM) may provide a good alternative solution to overcome such limitations. Scaffold materials can be combined together with plasmid DNA and a chemical-based transfection agent to form GAM, through which transfected cells could secrete growth factors in a sustained manner over a longer time duration; thereby enabling bone graft materials to act as a repository of therapeutic genes, while providing structural support and a scaffold matrix for new bone tissue ingrowth. In this study, we prepared hydroxyapatite/chitosan-microspheres (HA/CS-MS) with microfabrication technology and emulsification method, and loaded the polyethylene imine/bone morphogenetic protein 2 plasmid (PEI/pBMP2) complexes with high transfection capacity (transfection efficiency up to 54.79% ± 4.95%), thus forming a novel GAM system with superior bone regeneration capacity—PEI/pBMP2-HA/CS-MS. The in vitro experiments in this study demonstrated that our GAM had excellent biocompatibility (with cell viability over 95%), and that the as-fabricated microsphere material possessed a nano-network fibrous structure similar to natural extracellular matrix (ECM), together with a higher surface area that can provide more cell adhesion sites. The sizes of the prepared microspheres were mainly distributed in the 160–180 µm range, while the maximal loading rate of PEI-pBMP2 complexes was 59.79% ± 1.85%. As a loaded complexes system, the GAM can release plasmids in a slow controlled manner, effectively transfecting surrounding target cells (release effect for up to 21 days), while cells adherent to the material can also take up plasmids, resulting in sustained secretion of the target protein, thereby effectively promoting bone regeneration. In vivo data from micro-computed tomography (micro-CT) and histological staining showed that the use of the composite materials effectively enhanced bone regeneration in defect areas. These findings thus demonstrated that the novel GAM system had excellent osteoinductivity with significant clinical potential.